Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) dengan Penambahan Pupuk Organik Cair Urin Sapi yang Ditambahkan dengan Kotoran Kelelawar - Untung Santoso; Hendriyanto Hendriyanto; Akhmad Rizali (Universitas Lambung Mangkurat, 2021)
Mustard greens (Brassica juncea L) is one of the most popular leaf vegetable horticultural commodities because it has a delicious taste, is easy to obtain and is relatively easy to cultivate. The use of cow urine liquid organic fertilizer with the addition of bat manure as a nutrient provider that is needed by plants during plant growth that contributes to the yields obtained by plants. This study aims to determine the suitability of N, P and K nutrient status in cow urine liquid organic fertilizer with the addition of bat manure according to the 2009 Ministry of Agriculture and to determine the effect of liquid organic fertilizer cow urine with the addition of bat manure on the growth and yield of mustard greens. This study used RAL with one factor in the form of several doses of bat manure with 5 levels of treatment, namely P0 (control) = 100 mL of cow urine POC, P1 = 100 mL POC cow urine 15 grams of bat dung, P2 = 100 mL POC cow urine 20 gr. bat manure, P3 = 100 mL POC cow urine 25 gr bat dung, P4 = 100 mL POC cow urine 30 gr bat dung. The results of this study indicated that the POC treatment of cow urine with the addition of bat manure did not significantly affect plant height, number of leaves, leaf width and wet weight of mustard greens.